(untitled) (Research, Society and Development, 2020)
Objective: we used the distribution of circular probabilities of von Mises to determine the predominant wind direction in Patos, Paraíba. Method: we used hourly data of circular wind direction, obtained by the National Institute of Meteorology - INMET, from July 21, 2007 to September 30, 2018. Circular statistics were applied to the data, more precisely, the von Mises distribution. Results: The results of the analyses showed that the von Mises distribution adjusted well to the wind direction data, verifying that the wind direction in this municipality is with a high variation in the Southeast direction. Conclusion: The analysis allowed to be a useful tool for a possible installation of a wind farm, obtaining a greater use of the wind direction in the locality.